2011
DOI: 10.1038/pr.2011.29
|View full text |Cite
|
Sign up to set email alerts
|

Preterm birth with antenatal corticosteroid administration has injurious and persistent effects on the structure and composition of the aorta and pulmonary artery

Abstract: INTRODUCTION:Preterm birth affects 8-12% of live births and is associated with the development of elevated arterial blood pressure and aortic narrowing in later life; this suggests that preterm birth may alter the development of arteries. Our objective was to determine the effects of preterm birth, accompanied by antenatal corticosteroid administration, on the structure of the aorta and pulmonary artery, which experience different alterations in pressure flow at birth. RESULTS: at 11 wk, preterm lambs had sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“…Nevertheless, we found that antenatal glucocorticoid exposure is associated with a localised increase in aortic arch stiffness in preterm-born young adults, similar in magnitude to term-born individuals a decade older [16]. This is in line with findings in animal models, which have demonstrated a specific effect of antenatal glucocorticoid exposure on connective tissue accumulation and arrangement within the aortic wall in late gestation [48].…”
Section: Antenatal Glucocorticoidssupporting
confidence: 90%
“…Nevertheless, we found that antenatal glucocorticoid exposure is associated with a localised increase in aortic arch stiffness in preterm-born young adults, similar in magnitude to term-born individuals a decade older [16]. This is in line with findings in animal models, which have demonstrated a specific effect of antenatal glucocorticoid exposure on connective tissue accumulation and arrangement within the aortic wall in late gestation [48].…”
Section: Antenatal Glucocorticoidssupporting
confidence: 90%
“…Interestingly, we reported that neonatal oxidative stress plays a key role in programming elevated blood pressure and vascular dysfunction in the low protein diet model [57]. In another study, preadolescent normotensive lambs (9 weeks) which had been delivered prematurely (at 0.9 gestation) show remodeling of the aortic wall with increased thickness, increased elastin deposition, reduced smooth muscle content but unchanged collagen content [24]. Differences between these studies and the current report are not all elucidated but can be related to differing type of stressor (restricted diet vs. oxygen), timing of insult, and species studied.…”
Section: Discussionmentioning
confidence: 90%
“…The area of the tunica media was calculated by subtracting the first area from the second area. Secondly, the density of elastin fibres (Verhoeff-Van Gieson stain) and of collagen fibres (Masson's trichrome stain) were quantified using the image analysis software (as above) and the ratio of their respective densities to the surface of the tunica media area was calculated [24]. Three to four series of sections per rat were studied and averaged.…”
Section: Methodsmentioning
confidence: 99%
“…Subsequent to studies in the sheep describing the effect of preterm birth on the developing cardiovascular system , two clinical studies have compared cardiac growth and function in young adults born either preterm or term, using magnetic resonance imaging (MRI) . In the first of these two studies, it was shown that preterm birth was associated with an increase in left ventricular wall mass, abnormal wall geometry (a reduced internal chamber diameter, the left ventricular free wall was shorter, and the apex of the left ventricle was no longer centered normally), and systolic and diastolic dysfunction in the left ventricle.…”
Section: Introductionmentioning
confidence: 99%